2017
DOI: 10.1111/1467-9604.12182
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences of academic success with dyslexia: A call for alternative intervention

Abstract: This article describes a small‐scale study exploring the perspectives of five undergraduate students with dyslexia. Semi‐structured interviews were conducted in two universities in the UK. The interviews explored participants’ perceptions of their dyslexia label and how it had affected their academic success. The aim of the research was to identify facilitating factors that supported participants with dyslexia during their education. The following themes were identified: age of dyslexia identification, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…Pitt and Soni (2018) and Robinson (2017) identified key elements for academic success among persons diagnosed with dyslexia. For instance, early diagnosis is an imperative element of future academic success.…”
Section: General Strategies In Promoting Academic Success Among Perso...mentioning
confidence: 99%
See 4 more Smart Citations
“…Pitt and Soni (2018) and Robinson (2017) identified key elements for academic success among persons diagnosed with dyslexia. For instance, early diagnosis is an imperative element of future academic success.…”
Section: General Strategies In Promoting Academic Success Among Perso...mentioning
confidence: 99%
“…For instance, early diagnosis is an imperative element of future academic success. Qualitative investigations found that the lack of a diagnosis and/or lack of the correct diagnosis may limit learning potential among students, especially Black males (Pitt & Soni, 2018; Robinson, 2017). School counselors engaged as advocates and promoters of the MTSS process may assist in proper identification of Black students’ academic and social/emotional needs and further develop more appropriate, culturally relevant interventions.…”
Section: General Strategies In Promoting Academic Success Among Perso...mentioning
confidence: 99%
See 3 more Smart Citations